[tex]\\ \rm\rightarrowtail 6^{x+2}=8[/tex]
[tex]\\ \rm\rightarrowtail (6)^{x+2}=2^3[/tex]
[tex]\\ \rm\rightarrowtail ln6^{x+2}=ln2^3[/tex]
[tex]\\ \rm\rightarrowtail (x+2)ln6=3ln2[/tex]
[tex]\\ \rm\rightarrowtail xln6+2ln6=3ln2[/tex]
[tex]\\ \rm\rightarrowtail xln6+2ln2+2ln3=3ln2[/tex]
[tex]\\ \rm\rightarrowtail xln6+2ln3=3ln2-2ln2[/tex]
[tex]\\ \rm\rightarrowtail xln6+2ln3=ln2[/tex]
[tex]\\ \rm\rightarrowtail xln3+xln2+2ln3=ln2[/tex]
[tex]\\ \rm\rightarrowtail (x+2)=\dfrac{ln8}{ln6}[/tex]
[tex]\\ \rm\rightarrowtail x=\dfrac{ln8}{ln6}-2[/tex]
Another
[tex]\\ \rm\rightarrowtail (x+2)ln6=ln8[/tex]
[tex]\\ \rm\rightarrowtail (x+2)ln6=ln2^3[/tex]
[tex]\\ \rm\rightarrowtail (x+2)ln6=3ln2[/tex]
[tex]\\ \rm\rightarrowtail x+2=\dfrac{3ln2}{ln6}[/tex]
[tex]\\ \rm\rightarrowtail x=\dfrac{3ln2}{ln6}-2[/tex]